Abdominal incisional endometrioma following cesarean section: a case report - Laohapensang K. (2014)
A 34 year old woman underwent a cesarean section for placenta previa when she was 25 years old, after that she took oral contraceptives regularly for 8 years and remained asymptomatic. Upon entering our hospital, the patient stopped taking the oral contraceptives and had a one year history of cyclic bleeding from the lower midline abdominal incision scar. Surgical excision was done and pathological findings revealed endometrioma.